External Adjustments and Exchange Rate Flexibility: Some Evidence from U.S. Data - Kim, Yoonbai (The Review of Economics and Statistics, 1991)
This paper examines the role of the exchange rate in U.S. external adjustments. The results show that the exchange rate is an important transmission channel of influence on prices, and with longer lags, on income and the trade balance. The effects of the exchange rate and relative prices on the trade balance are not symmetric even in the long run. Exchange rate feedback is insignificant and makes little difference in trade balance adjustment. There are also indications that the response of relative prices to the exchange rate shifted in recent years. Such changes seem to help explain the persistence of the U.S. trade deficit in recent years for multilateral trade, but not bilateral trade, with Japan or Germany. Copyright 1991 by MIT Press.